Social Facilitation in Fear Appeals Creates Positive Affect but Inhibits Healthy Eating Intentions - Bailey, Rachel L.; Wang, Tianjiao Grace; Liu, Jiawei; Clayton, Russell B.; Kwon, Kyeongwon; Diwanji, Vaibhav; Karimkhanashtiyani, Farzaneh (Frontiers in Psychology, 2022)
The social facilitation of eating plays a significant role in influencing individuals’ eating decisions. However, how social eating cues are processed in health promotion messages is unclear. This study examined individuals’ food craving in response to social cues in images (Experiment 1) and emotional experiences, perceived threat, perceived efficacy, behavioral intentions, and motivational coactivation elicited by social eating cues in obesity prevention fear appeals (Experiment 2). Results suggested that the presence of a group of people eating in an image facilitated food craving for the presented foods. Moreover, fear appeals that presented obesity and its consequences with more social eating cues, versus individual eating cues, generated greater positive emotional responses, perceived threat severity, response and self-efficacy, and motivational coactivation indicating more attention and threat vigilance. However, these cues also generated fewer self-reported intentions to change unhealthy eating behaviors. Implications and suggestions for future research are discussed.